Detection of putative periodontopathic bacteria in type 1 diabetic and healthy children: A comparative study - Ponnudurai Arangannal; Santoshkumari; Padma Krishnan; Mamta Harilal Nichani; Mahalakshmi Krishnan; Vishnurekha Chamarthi (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of this study was to compare and assess the risk of periodontitis due to the presence of four putative periodontopathic bacteria (Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, and Aggregatibacter actinomycetemcomitans) in type 1 diabetic and healthy children. Materials and Methods: Fifty type 1 diabetic and 50 healthy children in the age group of 7-14 years were recruited for the study. Subgingival plaque samples collected from permanent first molars were subjected to polymerase chain reaction assay to detect 16S rRNA gene of P. gingivalis, T. forsythia, T. denticola and A. actinomycetemcomitans. The data were analyzed using Fisher exact test. The P < 0.05 was considered statistically significant. Results: The prevalence of subgingival periodontal pathogens in diabetic and healthy children was 2% and 4% for P. gingivalis, 34% and 34% for T. denticola, 20% and 18% for A. actinomycetemcomitans and for T. forsythia, 4% and 34%, respectively. Significant statistical difference was not observed with regard to the prevalence of P. gingivalis, T. denticola, and A. actinomycetemcomitans among type 1 diabetic and healthy children (P = 1.00). Conversely, T. forsythia was less prevalent in diabetic children compared to healthy children. Conclusion: Statistical significance was not observed for the prevalence of periodontopathic bacteria in type 1 diabetic subjects. The results of the present study thus reveal the absence of risk of periodontitis by these bacterial species in type 1 diabetic subjects.